A Rare Case of Calciphylaxis: A Case Report - Maria Lafrid; Narjiss Labioui; Mohamed Hallak; Abdelaali Bahadi; Driss El Kabbaj; Mohamed Allaoui; Yassir Zajjari (Biomedicine Hub)
Introduction: Calciphylaxis is a rare and severe disorder characterized by obstructive small vessel disease in the subcutaneous adipose tissue and skin, leading to necrotic skin lesions. The condition poses a significant risk of mortality due to infectious and ischemic complications. Case Presentation: We present the case of a 60-year-old woman, with a history of renal lithiasis, hypertension, and end-stage renal disease on hemodialysis complicated by hyperparathyroidism and aortic valve replacement. She developed extensive necrotic lesions on both lower limbs and upper extremities, prompting a diagnosis of calciphylaxis. Radiographic and biopsy findings supported the diagnosis, revealing characteristic calcifications. Treatment involved antibiotics, oral thiosulfate, daily hemodialysis, hyperbaric oxygen therapy, and discontinuation of calcium and alfacalcidol, with alendronate initiation. Unfortunately, despite these interventions, the patient experienced a rapid clinical decline, developing septic shock necessitating bilateral leg amputations. Regrettably, she succumbed to the disease 10 days later. Conclusion: This case underscores the challenging prognosis of calciphylaxis and the need for effective therapeutic options, including surgical intervention and access to injectable thiosulfate.